Early economic evaluation to guide the development of a spectroscopic liquid biopsy for the detection of brain cancer. (24th February 2021) - Gray, Ewan; Cameron, James M.; Butler, Holly J.; Jenkinson, Michael D.; Hegarty, Mark G.; Palmer, David S.; Brennan, Paul M.; Baker, Matthew J.
Abstract: Objectives: An early economic evaluation to inform the translation into clinical practice of a spectroscopic liquid biopsy for the detection of brain cancer. Two specific aims are (1) to update an existing economic model with results from a prospective study of diagnostic accuracy and (2) to explore the potential of brain tumor-type predictions to affect patient outcomes and healthcare costs. Methods: A cost-effectiveness analysis from a UK NHS perspective of the use of spectroscopic liquid biopsy in primary and secondary care settings, as well as a cost–consequence analysis of the addition of tumor-type predictions was conducted. Decision tree models were constructed to represent simplified diagnostic pathways. Test diagnostic accuracy parameters were based on a prospective validation study. Four price points (GBP 50-200, EUR 57-228) for the test were considered. Results: In both settings, the use of liquid biopsy produced QALY gains. In primary care, at test costs below GBP 100 (EUR 114), testing was cost saving. At GBP 100 (EUR 114) per test, the ICER was GBP 13, 279 (EUR 15, 145), whereas at GBP 200 (EUR 228), the ICER was GBP 78, 300 (EUR 89, 301). In secondary care, the ICER ranged from GBP 11, 360 (EUR 12, 956) to GBP 43, 870 (EUR 50, 034) across the range of test costs. Conclusions: The results demonstrate the potential for the technology to be cost-effective in both primary and secondary care settings. Additional studies of test use in routine primary care practice are needed to resolve the remaining issues of uncertainty—prevalence in this patient population and referral behavior.